For too long, public figures have lived in fear of Murdoch. (New Statesman, 2011)
The article discusses what the author considers to be abusive behavior by British newspapers such as "News of the World" owned by medial mogul Rupert Murdoch. In the author's view public officials have been reluctant to criticize transgressions such as the hacking of a missing girl's voice-mail messages because they fear Murdoch, whose newspapers account for 40% of total circulation in Britain.